Maternal Diet During Gestation and Lactation Modifies the Severity of Salt-Induced Hypertension and Renal Injury in Dahl Salt-Sensitive Rats. Issue 2 (February 2015) - Geurts, Aron M.; Mattson, David L.; Liu, Pengyuan; Cabacungan, Erwin; Skelton, Meredith M.; Kurth, Theresa M.; Yang, Chun; Endres, Bradley T.; Klotz, Jason; Liang, Mingyu; Cowley, Allen W.
<x xml:space="preserve">Abstract</x> Environmental exposure of parents or early in life may affect disease development in adults. We found that hypertension and renal injury induced by a high-salt diet were substantially attenuated in Dahl SS/JrHsdMcwiCrl (SS/Crl) rats that had been maintained for many generations on the grain-based 5L2F diet compared with SS/JrHsdMcwi rats (SS/Mcw) maintained on the casein-based AIN-76A diet (mean arterial pressure, 116±9 versus 154±25 mm Hg; urinary albumin excretion, 23±12 versus 170±80 mg/d). RNAseq analysis of the renal outer medulla identified 129 and 82 genes responding to a high-salt diet uniquely in SS/Mcw and SS/Crl rats, respectively, along with minor genetic differences between the SS substrains. The 129 genes responding to salt in the SS/Mcw strain included numerous genes with homologs associated with hypertension, cardiovascular disease, or renal disease in human. To narrow the critical window of exposure, we performed embryo-transfer experiments in which single-cell embryos from 1 colony (SS/Mcw or SS/Crl) were transferred to surrogate mothers from the other colony, with parents and surrogate mothers maintained on their respective original diet. All offspring were fed the AIN-76A diet after weaning. Salt-induced hypertension and renal injury were substantially exacerbated in rats developed from SS/Crl embryos transferred to SS/Mcw surrogate mothers. Conversely, salt-induced hypertension and renal injury were significantly attenuated in rats developed from SS/Mcw embryos transferred to SS/Crl surrogate mothers. Together, the data suggest that maternal diet during the gestational–lactational period has substantial effects on the development of salt-induced hypertension and renal injury in adult SS rats.